1985
DOI: 10.1002/jsfa.2740360208
|View full text |Cite
|
Sign up to set email alerts
|

Some physical and chemical characteristics of Sri Lankan nutmeg oil

Abstract: Approximately 80 samples of Sri Lankan nutmeg oil (both industrially produced and laboratory distilled) were examined for relative density, optical rotation and refractive index and also analysed by gas chromatography. Results showed that although the oil resembled the West Indies type nutmeg oil rather than the East Indies type it had distinguishing features. Results of studies on industrially produced samples were as follows: relative density (3OoC/3O0C), 0.8690t0.0085; optical rotation (30"C), 31.722.7'; re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The specific gravity of the studied essential oil was 0.890,Sarath-kumara [22] have mentioned that the specific gravity of the East Indian Nutmeg oil ranges from 0.885 to 0.915 and that of west Indian has been 0.860 to 0.88 at 20˚ C. Leela [14] has also report that the specific gravity of east Indian oil is ranging from 0.880 to 0.913 and that of west Indian is ranging from 0.859 to 0.865.…”
Section: Resultsmentioning
confidence: 94%
“…The specific gravity of the studied essential oil was 0.890,Sarath-kumara [22] have mentioned that the specific gravity of the East Indian Nutmeg oil ranges from 0.885 to 0.915 and that of west Indian has been 0.860 to 0.88 at 20˚ C. Leela [14] has also report that the specific gravity of east Indian oil is ranging from 0.880 to 0.913 and that of west Indian is ranging from 0.859 to 0.865.…”
Section: Resultsmentioning
confidence: 94%
“…Also the value is in the range of refractive index of East Indian nutmeg oil mentioned by Sarath-kumara et al [30].…”
Section: Sensory Evaluation For the Essential Oilmentioning
confidence: 69%
“…Sarath-kumara et al [28] have mentioned that the specific gravity of the East Indian Nutmeg oil ranges from 0.885 to 0.915 and that of west Indian has been 0.860 to 0.88 at 20˚C, Leela [7] has also report that the specific gravity of east Indian oil is ranging from 0.880 to 0.913 and that of west Indian is ranging from 0.859 to 0.865. Reineccius [29] have reported that the specific gravity of east Indian has been 0.880 -0.910 and of west Indian has been 0.854-0.880 at 25˚C.…”
Section: Sensory Evaluation For the Essential Oilmentioning
confidence: 98%
“…Compositional data are presented from Baldry et al (1976) on East and West Indian oil, and Sarath-Kumara, Jansz and Dharmadasa (1985) on Sri Lankan oil (Table 7-59).…”
Section: Oil Of Nutmegmentioning
confidence: 97%